There are two roads marked out to us for the discovery of what we seek… Eunomius’ arguments on the generation of the Son based on the concepts of substance and activity - Stępień, Tomasz (Vox Patrum, 2018)
Eunomius of Cyzicus in his writings defends Arian understanding of the generation of the Son of God. He claims that the generation must be perceived as creation of the new essence. Therefore, the Son of God is the first creation and could not be equal with the Father. Among many arguments that he gives to support his thesis, he also evokes the distinction between essence (oÙs…a) and activity (™nšrgeia). Eunomius proposes his own methodology and states that there are two ways leading to proper understanding of generation. First one leads form the recognizing of the essence of God to conclusions on the generation, which is the activity of the Father. Another way of demonstration starts from the activities and allows distinguishing essences according to the products that they have caused. Eunomius underlines that both ways of enquiry lead to an irrefutable conclusion that the Father and the Son cannot have the same essence. Moreover, he claims that there could be no likeness between the two essences of the Father and the Son. The goal of this article is to review Eunomius’ arguments from the viewpoint of their effectiveness and proposed methodology. The orthodox answer of Basil the Great and Gregory of Nyssa are the context of reviewing Neo- Arian claims.